Addicting via hashtags: How is Twitter making addiction? - Dwyer, Robyn; Fraser, S. (Federal Legal Publications, Inc, 2016)
Persons, substances, bodies, consumption: an ever widening process of ‘‘addicting’’ is underway in Western societies. In this article, we turn our attention to the production of addiction on the microblogging social media platform, Twitter, as an important emerging site in which the addicting of contemporary societies is also occurring. Our analysis explores two questions. First, we investigate the ways in which addiction is enacted via Twitter. How is addiction being made on Twitter? Second, we ask how the technology of Twitter itself is shaping meaning: how do the technological ‘‘affordances’’ of Twitter help constitute the kinds of addiction being materialized? While we find a multiplicity of meanings in the 140-character messages, we also find a pattern: a tendency toward extremes—addiction riven between pain and pleasure. In addition, we find significant areas of commonality between approaches and notable silences around alternatives to common understandings of addiction. We argue that the constraints on communication imposed by Twitter technology afford a ‘‘shorthand’’ of addiction that is both revealing and productive. Illuminated is the importance of addiction as a piece of cultural shorthand that draws on and simultaneously reproduces simplistic, reductive addiction objects. In concluding, we consider what these realities of addiction being enacted through Twitter can tell us about contemporary conditions of possibility for drug use in society and for individual subjectivities and experiences.